2013
DOI: 10.5588/ijtld.12.0784
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to tuberculosis care for drug users in two provinces of China: a qualitative study

Abstract: These findings suggest that barriers to TB care for drug users are associated not only with the drug users themselves, but also with the providers and societal factors. Health professionals and policy makers should be aware of these barriers in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Third, an inductive coding approach combined with authors’ discussion of the themes developing in the analysis improved the accuracy of the data interpretation. Finally, the social issues raised in our study (e.g., stigma) were in general consistent with the literature relating to drug users [ 31 33 ]. Whereas for all of the limitations in the present study, our future study should attempt to involve more diverse participants, including drug users at other situations (community or voluntary settings), key informants or stakeholders to improve the validity of participants’ narratives and derive more convincing findings.…”
Section: Discussionsupporting
confidence: 89%
“…Third, an inductive coding approach combined with authors’ discussion of the themes developing in the analysis improved the accuracy of the data interpretation. Finally, the social issues raised in our study (e.g., stigma) were in general consistent with the literature relating to drug users [ 31 33 ]. Whereas for all of the limitations in the present study, our future study should attempt to involve more diverse participants, including drug users at other situations (community or voluntary settings), key informants or stakeholders to improve the validity of participants’ narratives and derive more convincing findings.…”
Section: Discussionsupporting
confidence: 89%
“…In China, a number of studies have been conducted into women’s knowledge and attitudes toward cervical cancer screening and related factors,11–14 however most data have been quantitative in nature 12–14. This leaves local gaps in understanding of underlying determinants of care-seeking, including the reasons why women do not take up free care, which require more qualitative research approaches 15 16. This research aimed to gain a deeper understanding of the barriers to uptake of free cervical cancer screening by rural women in Jining Prefecture, using a design that can suggest new policy and practice approaches that may be able to increase future uptake and reduce the burden of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Research, though in other settings, revealed TB related stigma as a key barrier to adequate TB screening rates [22][23][24].…”
Section: Introductionmentioning
confidence: 99%